The Influence of Breastfeeding Technique Education on the Effectiveness of Postpartum Mothers in Breastfeeding in the Working Area of the Tanjung Kota Sungai Penuh Health Center, Indonesia - Zaini, Hanifa; Radhia, Mekar Zenni; Silvia, Elwitri; Weri, Tara Nilma (HM Publisher, 2024)
Breastfeeding is the best way to feed a baby. However, many postpartum mothers experience difficulty in breastfeeding. Education about correct breastfeeding techniques can help postpartum mothers breastfeed effectively. This study aims to determine the effect of education on breastfeeding techniques on the effectiveness of postpartum mothers in breastfeeding in the working area of the Tanjung Kota Sungai Penuh Health Center, Indonesia. This research used a quasi-experimental design with a pre-test and post-test with a control group design. A total of 60 postpartum mothers were randomly divided into two groups, namely the intervention group (n=30), who received education on breastfeeding techniques, and the control group (n=30), who did not receive education. The effectiveness of breastfeeding was measured using a questionnaire. Data were analyzed using the Mann-Whitney U test. The results showed that there was a significant difference between the intervention group and the control group in terms of the effectiveness of breastfeeding after the intervention (p=0.001). Education on breastfeeding techniques has been proven to be effective in increasing the effectiveness of postpartum mothers in breastfeeding.